Eksistensi Lembaga Pendidikan Pesantren Salaf Di Tengah Arus Modernitas - Imam Sucipto (STAI Siliwangi Bandung, 2022)
The existence of Salaf Islamic boarding schools must follow developments and modernization in every aspect of its development. Salaf Islamic boarding schools must open themselves from the rapid progress and development of the outside world anpud must be able to understand their needs and demands. The existence of the Salaf Islamic boarding school certainly must be able to color the stage of modernity to face the global challenges of the outside world must be able to adapt and interact by not leaving and eliminating the values of salafiyah purity in accepting the development activities of the times. Of course, too, modernity has many advantages, but besides that, many possibilities must be avoided. Islamic must watch out for progress in the field of technology boarding schools in general, the rapid development of technology should not then make the collapse of the pure values of Islamic teachings in salaf boarding schools just the opposite of how Salaf Islamic boarding schools can use this information technology as a means to develop and promote education and teaching in Islamic boarding schools